2021
DOI: 10.1111/bju.15530
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour DNA reveals genetic traits of patients with intraductal carcinoma of the prostate

Abstract: To investigate the genetic alterations of patients with prostate cancer (PCa) with and without intraductal carcinoma of the prostate (IDC-P). Patients and MethodsWe performed targeted sequencing of plasma cell-free DNA on 161 patients with prostate adenocarcinoma (PAC) with IDC-P and 84 without IDC-P. Genomic alterations were compared between these two groups. The association between genetic alterations and patients' survival outcomes was also explored. ResultsWe identified that 29.8% (48/161) and 21.4% (18/84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…More than one-third (35.6%) of IDC-P-positive cases had alterations of DNA repair pathways in the CRPC cohorts, and this finding was approximately 10% higher than the results from previous studies [ 20 ]. More interestingly, pathogenic germline mutations in DNA repair genes, including BRCA2 and CDK12 , were more frequently detected in patients with IDC-P than in those without IDC-P. For instance, the prevalence of germline BRCA2 mutations was significantly higher in patients with IDC-P than in those with adenocarcinoma of the prostate (8.7% vs. 0%, respectively) [ 20 ]. For IDC-P carriers at CRPC status, patients with BRCA2 mutation showed shorter PSA-PFS after first-line abiraterone acetate administration (median 9.1 versus 11.9 months).…”
Section: Genomic Alterations Of Idc-pcontrasting
confidence: 55%
See 4 more Smart Citations
“…More than one-third (35.6%) of IDC-P-positive cases had alterations of DNA repair pathways in the CRPC cohorts, and this finding was approximately 10% higher than the results from previous studies [ 20 ]. More interestingly, pathogenic germline mutations in DNA repair genes, including BRCA2 and CDK12 , were more frequently detected in patients with IDC-P than in those without IDC-P. For instance, the prevalence of germline BRCA2 mutations was significantly higher in patients with IDC-P than in those with adenocarcinoma of the prostate (8.7% vs. 0%, respectively) [ 20 ]. For IDC-P carriers at CRPC status, patients with BRCA2 mutation showed shorter PSA-PFS after first-line abiraterone acetate administration (median 9.1 versus 11.9 months).…”
Section: Genomic Alterations Of Idc-pcontrasting
confidence: 55%
“…Exome sequencing data from The Cancer Genome Atlas (TCGA) showed that patients with IDC-P components had higher rates of point mutations in FOXA1 (15% vs. 5%), TP53 (19% vs. 10%), and SPOP (19% vs. 10%) than in those without IDC-P [ 32 ]. In addition, IDC-P carriers had a unique AR pathway aberration, such as enrichment of NCOR2 mutation, compared with individuals with pure prostate adenocarcinoma [ 20 ].…”
Section: Genomic Alterations Of Idc-pmentioning
confidence: 99%
See 3 more Smart Citations